Peran Pembelajaran Prakarya terhadap Perkembangan Motorik Halus dan Kasar Siswa di SMP Muhammadiyah 57 Medan - Situmorang , Dhiya Tsabitah; Salsabila, Nazwa; Syabila, Tiara; Narpila, Suci Dahlya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to investigate the role of craft learning in the development of fine and gross motor skills among students at SMP Muhammadiyah 57 Medan. The method used is a qualitative approach with a case study design. The study involved seventh and eighth-grade students engaged in craft learning activities over a specific period. Data were collected through interviews, observations, and documentation, with data analysis using descriptive techniques. The results showed that craft learning positively impacted the development of fine motor skills, such as drawing and assembling skills, as well as gross motor skills, including balance improvement and physical strength. Craft learning that involves various physical activities helps to improve body coordination, increase muscle strength, and enhance students’ gross motor abilities. Therefore, craft learning plays an essential role in supporting the development of both fine and gross motor skills, which positively influences students’ physical and cognitive abilities.